Analysis of Implementation of Minimum Wage Determination Policies in Indonesia - Khotim Fadhli; Zulfa Ulin Nuha (Cita Konsultindo Research Center, 2022)
The minimum wage is one of the government's interventions in the employment field that has been implemented by more than 90% of countries in the world. Although it has been practised for over four decades, the Indonesian minimum wage is still controversial in its implementation. This study uses a qualitative approach and retrospective descriptive technique. This study analyses Indonesia's minimum wage determination policies and their implementation. This study updates previous research on the Indonesian minimum wage policy. The result of this study shows that the minimum wage policies are divided into five periods. Policies in each period undergo change adjusting to economic conditions. But in their implementation, every minimum wage policy is considered profitable only partly. It happens because the minimum wage is a practical problem, which causes different impacts in different conditions. The minimum wage issue is the conflict between two social classes in capitalism: the bourgeoisie and the proletariat.